Manajemen Dakwah dalam Al-Qur’an - Hasanudin Hasanudin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2006)
Management is an activity, its implementer is called a manager, and the implementation process is called management. Management encompasses activities to achieve goals, carried out by individuals who contribute their best efforts through actions that have been done previously. This includes knowledge of what they should do, determining how to do it, understanding how they should do it, understanding how to organize and manage the effectiveness of their efforts. Examining the Quran with a management approach, especially in the context of da’wah management and its practice during the time of the Prophet Muhammad (peace be upon him), is a top priority in this discussion.